PENGARUH NAPTHALENE ACETIC ACID DAN BENZYL AMINO PURINE TERHADAP MIKROPROPAGASI TANAMAN AKAR WANGI (Vetiveria zizanioides L. Nash) - Rama Adi Pratama; Yunira Rahmaningsih; Noertjahyani Noertjahyani; Kelik Putranto; Raden Haerudjaman (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2022)
Vetiver grass (Vetiveriazizanioides L. Nash) is one of the oil-producing plants essential. Tissue culture is one of the way to increase the availability of superior seeds of vetiver (Vetiveriazizanioides L. experiment was carried out at the Integrated Laboratory of the Faculty of Agriculture, Garut University from July to August 2020. This experiment used a Factorial Complete Randomized Design consisting of two factors, the first factor is NAA (N) with three levels of concentration, n1 =0, 5 mg / l, n2 = 1,5 mg/l, n3 = 2,5 mg/l varieties Verina 1. The purpose of this study was to obtain independent interactions and effects between Napthalene Acetic Acid (NAA) and Benzyl Amino Purine(BAP) on the micropropagation of vetiver plants (Vetiveriazizanioides L. Nash) variety Verina 1for 30 DAP. This 5 mg / l, n3 = 2.5 mg / l. The second factor is BAP (B) with two levels of concentration, b1 = 0.5 mg / l, b2 = 3 mg / l. The observed variables are: root emergence time, root number, callus appearance time, callus number, callus color and growth percentage. The results showed that there was no interaction between NAA and BAP, but there was an independent influence on the observed parameters of root emergence time, number of roots, callus appearance time and number of callus. The best concentration of NAA is 0.5 mg / l. The percentage of growth shows the yield of growth that is 100%.